Evaluation of the ornamental potential of pepper genotypes based on factor analysis (Research, Society and Development, 2020)
The ornamental pepper market has been growing in recent years, nationally and internationally, and has stimulated the development of breeding programs aimed at new pepper varieties with desirable characters for the ornamental market. The use of factor analysis is a multivariate technique that allows to reduce a set of variables in a reduced number of latent factors, which facilitates the study of a set of data. The objective of the present work was to evaluate the ornamental potential of pepper genotypes based on factor analysis. 29 Capsicum annnuum genotypes were evaluated, based on 12 quantitative traits, in a completely randomized design, with 5 replications. The 12 characteristics evaluated were summarized in 3 factors: fruit quality (8 variables), plant size (2 variables) and plant architecture (2 variables). Within each factor then the variables that are highly correlated. The factor values were predicted through the scores. Through these, graphics were made to verify the behavior of C. annuum genotypes in relation to the factors obtained. 12 genotypes were selected as those with the greatest potential for ornamentation and can be used in future crosses.